Perbedaan Gaya Pengajaran Dosen Universitas Asahan Kisaran - Hasanuddin Hasanuddin (Mahesa Research Center, 2020)
This study aims to look at the differences in teaching style of the UNA Kisaran lecturers, the method used is quantitative, a population of 123 lecturers and all of them are sampled. The instrument uses the Grasha 1996 teaching style scale. The results showed that there were some differences based on gender, experience, age and majors seen from the three teaching styles, all showing significant differences. The results of the T test show there are differences in teaching styles seen from the gender and majors of lecturers. The results of ANOVA showed teaching experience and age between the range 5-12, 13-20 and> 21 years also showed differences. Anova results show that age gives a difference between 31-40, 41-50 and> 51 years. Then between the sexes of men and women also provide a significant difference.